Corporate Social Responsibility (CSR) sebagai Aktualisasi Zakat, Infaq dan Shadaqah (ZIS) - Marfuah Sri Sanityastuti (Jurnal Komunikasi, 2009)
Corporate Social Responsibility (CSR) in Indonesia has been stated in constitution (UUD1945), some acts, and special regulations. Those are indicated that the implementation of CSR as a responsibility to local community is important Nevertheless, its implementation is still various. Black category is for company does not have CSR program, red category is for company holding CSR program within pressure, blue category is for company seeing CSR as investment, and green category is for company has noticed that CSR is its business heart As many as CSR arrangements, it is shown government intention to actualize Zakat, Infaq, and Shadaqah (ZIS) as a Moslem giving obligation to powerless other Moslem. To encourage company in implementing CSR appropriately, government shall control and sentence punishment to any company who does not implement it